2008
DOI: 10.1080/10407410701766643
|View full text |Cite
|
Sign up to set email alerts
|

Gestures and Phases: The Dynamics of Speech-Hand Communication

Abstract: We investigated how a listener's perceived meaning of a spoken sentence is influenced by the relative timing between a speaker's speech and accompanying hand gestures. Participants viewed a computer-animated character who uttered the phrase, "Put the book there now." while executing a simple right-handed beat gesture whose location relative to the utterance was precisely controlled in a frame-by-frame fashion. The participant's task consisted of making a judgment about two related aspects of the actor's percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 68 publications
(68 reference statements)
2
25
1
Order By: Relevance
“…It suggests that there are multiple positions in a sentence where gesture-speech integration can take place (for a similar notion for not semantically related gesture-speech integration, see Leonard & Cummins, 2011;Treffner et al, 2008). At the moment, we hypothesize that those positions are at the content words of the sentence, 7 but this needs further confirmation.…”
Section: Integration and Sentence Processing: Multiple Time Windows?mentioning
confidence: 88%
See 2 more Smart Citations
“…It suggests that there are multiple positions in a sentence where gesture-speech integration can take place (for a similar notion for not semantically related gesture-speech integration, see Leonard & Cummins, 2011;Treffner et al, 2008). At the moment, we hypothesize that those positions are at the content words of the sentence, 7 but this needs further confirmation.…”
Section: Integration and Sentence Processing: Multiple Time Windows?mentioning
confidence: 88%
“…Previous gesture research has shown that timing of gesture and speech information plays a crucial role in their integration (Habets et al, 2011;Leonard & Cummins, 2011;Obermeier et al, 2011;Treffner et al, 2008). When gesture and speech are in close synchrony, their integration is seemingly automatic or obligatory (for more details on the notion of automaticity see below, but see also Kelly, Özyürek, & Maris, 2010).…”
Section: A Time Window For Gesture-speech Integrationmentioning
confidence: 95%
See 1 more Smart Citation
“…In other words, he suggests that if gestures and speech are synchronous, they should be integrated in a rather automatic way. So far, however, there has been little empirical work on the effects of gesture-speech synchronization in comprehension (but see Treffner, Peter, & Kleidon, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Best (1995) and Fowler (1986Fowler ( , 1996 have proposed that speech, like other ecological events, can be directly perceived (Gibson, 1966;Kelley, 1986). Other investigators have explored language as a "coordination device" (Clark, 1996) in which people talking entrain in various ways with their own actions or with those of interlocutors (e.g., Giles, Coupland, & Coupland, 1991;Shockley, Santana, & Fowler, 2003;Treffner & Peter, 2002) and in which nonverbal aspects of speaking and listening (e.g., manual gestures) affect linguistic interpretation (Treffner, Peter, & Kleidon, 2008). As Cowley notes in his contribution to this issue, Gibson (e.g., 1979Gibson (e.g., /1986 himself wrote a little about language, usually focusing on utterances as instances of indirect (mediated) perception, more or less like picture perception.…”
Section: Making Room For Creativitymentioning
confidence: 99%